System of ownership and tenure of high Andean natural pastures - Casaverde R., Juvenal (1985)
Let us begin by indicating two facts of transcendental importance: first, that Peru is a privileged country because it has the largest volume of South American domestic camelids, since it has 2,450,000 alpacas and 1,200,000 llamas, which represent 90o/o and 30o/o of the global volume of these species, respectively. It is estimated that 80% of alpacas and almost all llamas are in the possession of small owners, basically organized in peasant communities that have livestock as the main source of their economy.